The Transformation Process of Chili Auction Market From Conventional to Digital in Kulonprogo Regency, Indonesia - Nurlaela, Siti; Raya, Alia Bihrajihant; Euriga, Epsi; Sujono, Sujono; Sukadi, Sukadi; Fitria, Ina; Panicara, Salsadila; Pradinata, Aviad Rezqiano; Syahadah, Muhammad Ali (Agro Ekonomi, 2025)
The digital transformation of auction market management plays a crucial role in addressing the high volume of chili peppers and mitigating potential inefficiencies and inaccuracies in operational processes. However, several challenges persist in implementing this transformation. Therefore, this study aimed to investigate the process of transitioning auction market management from conventional to digital. Using a descriptive qualitative methodology, insights were obtained from auction market managers representing five distinct groups in Kulon Progo Regency. Data collection methods included focus group discussions (FGDs), observation, and in-depth interviews. The results showed varying levels of readiness for digital adoption across the markets, with Tani Rejo Auction Market leading in digital technology utilization. Key factors influencing the pace and success of this transformation included institutional dynamics, leadership capabilities, and human resource preparedness. However, persistent farmers perceptions regarding the potential adverse impacts of digital pricing on livelihoods remained a barrier. This study outlined a phased transformation process, comprising initial communication, goal setting, system analysis, implementation of digital applications, training, socialization, evaluation, and follow-up. In addition, support from stakeholders, particularly the Agriculture Office and Bank Indonesia (BI), was identified as crucial in facilitating farmers and traders through the digitalization process, typically improving market efficiency and benefiting all stakeholders.